EXTERNAL MAGNETIC PULSE STRAIGHTENING – NEW TECHNOLOGY CAR BODY REPAIR - Gnatov, A.; Гнатов, А. В. (Харьковский национальный автомобильно-дорожный университет, 2015)
Innovative equipment of external contactless magnetic impulse straightening developed by the laboratory of Electromagnetic Technology of Kharkiv National Automobile and Highway University is presented in this paper. The effect of metal hyper-plasticity at magnetic impulse acting is described. Suggestions concerning practical testing of advanced technology of damaged car body panels by external contactless magnetic impulse straightening are presented. The processing route of external contactless magnetic impulse straightening process is specified.
ВНЕШНЯЯ МАГНИТНО-ИМПУЛЬСНАЯ РИХТОВКА – НОВАЯ ТЕХНОЛОГИЯ КУЗОВНОГО РЕМОНТА АВТОМОБИЛЕЙ
ЗОВНІШНЄ МАГНІТНО-ІМПУЛЬСНЕ РИХТУВАННЯ – НОВА ТЕХНОЛОГІЯ КУЗОВНОГО РЕМОНТУ АВТОМОБІЛІВ
Keywords: external straightening; dents removing; body repair; magnetic-pulse metal working; car body panels; внешняя рихтовка; удаление вмятин; кузовной ремонт; магнитно-импульсная обработка металлов; кузовная панель; зовнішнє рихтування; видалення вм’ятин; кузовний ремонт; магнітно-імпульсна обробка металів; кузовна панель; 621.318